The Effect of Government Regulation on Coal as Export Commodities and Downstream Effort Through Coal Liquefaction (Systems Dynamic Modelling Approach) - Yudianto Yudianto; Joko Tri Haryanto (Research and Development Agency Ministry of Home Affairs, 2018)
Coal is still treated as an export commodity. On the other hand, the government is expecting additional value from the coal sector, among other, through coal liquefaction. The role of the government has been demonstrated through regulation, but there have been no concrete results to realize the downstream effort of coal. To find out to what extent is the optimum coal composition between the coal exported as commodity and coal used for liquefaction, it is analyzed by systems dynamic modeling method in several scenarios. The results show that there are several scenarios that suitable as Government alternative by fine-tuning the royalty instrument and the portion of state revenue. Scenario II plausibly be the best proposal that is to seek coal for downstream effort through liquefaction in order to liquefy the coal by 50%, while still allocating the remaining portion for the sale of coal as a commodity. This is reinforced because factually there is portion of coal as a commodity being sold domestically as fuel of power plant (PLTU). In Scenario II, coal liquefaction begins to provide a positive cumulative cash flow difference to the baseline after assuming a pre-set condition of royalty at 0% and the state revenue portion in the range of 60% - 80%. The imposition of a royalty of 5% can still be maintained, provided that it remains collaborated with a decrease in the portion of state revenue. This is because the decline in the portion of state revenue is very significant in increasing the cumulative cash flow of coal liquefaction. The state revenue portion can be installed in the range of 60% - 70% on the grounds that this coal liquefaction activity is a process of increasing the value-added that has an impact on the economy.